Attempts to dispel the efforts of the Arab Islamic conquest of Andalusia between conspiracy and deception "92-95 AH" a critical analytical study - Lajlaj , Ass.Prof Dr. Ahmed Abdel-Kazem (Thi Qar Arts Journal, 2022)
Praise be to God, the Lord of the worlds, the owner of the clear cause, who inspired us and enabled us to search in the folds of the great Andalusian history that is familiar with the events that have always been and will be an important source from which every student of knowledge draws until we found ourselves in front of a sea full of information in the field of our specialization that prompted us to search, investigate and link ideas in the format of historical research scientifically systematic. Andalusia, from the conquest until the Arabs left it, was part of the important Islamic history, and this is what made us shed light on an important period, which is the period of the Arab conquest of the Iberian Peninsula 91-95 AH. (1) and Tariq bin Ziyad (2). This research presents an accurate picture of the course of the conquest from several points of view represented by the emergence of the leadership personality in addition to the fame in the field of leadership thought, and this is what prompted the leaders of the conquest to use these points in the Andalusian lands, in addition to that the crowding of the opposite fears of Musa and the caliphate, each of them had a special vision It was invested by the leaders Tariq and Mughith (3) and the two caliphs, Al-Walid and Suleiman, sons of Abd al-Malik later. The research presents these crises, but in detail.